2015
DOI: 10.1007/s11270-015-2604-2
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Based Water Treatment Residual Use in a Constructed Wetland for Capturing Urban Runoff Phosphorus: Column Study

Abstract: Aluminum-based water treatment residuals (Al-WTRs) have a strong affinity to sorb P. In a proofof-concept greenhouse column study, Al-WTR was surface-applied at rates equivalent to 0, 62, 124, and 248 Mg ha −1 to 15 cm of soil on top of 46 cm of sand;Al-WTR rates were estimated to capture 0, 10, 20, and 40 years of P from an urban watershed entering an engineered wetland in Boise, ID, USA. Creeping red fescue (Festuca rubra) was established in all columns; one set of columns received no Al-WTR or plants. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…For instance, work by Oladeji et al (2008) demonstrated that surface application of Al WTRs at 10 g kg −1 reduced the leachate P concentration by 46-54% in sandy soils amended with either poultry manure or sewage biosolids. In soil column experiments, Al WTR surface applications of 124 and 248 t ha −1 have proven to assist in the reduction of leached P from urban runoff (Ippolito 2015). Similarly, field studies found that Al WTR application at 22.4 dry t ha −1 can reduce leaching of P into shallow groundwaters ).…”
Section: Immobilisation Of Contaminants and Excess Nutrients In Soilmentioning
confidence: 92%
“…For instance, work by Oladeji et al (2008) demonstrated that surface application of Al WTRs at 10 g kg −1 reduced the leachate P concentration by 46-54% in sandy soils amended with either poultry manure or sewage biosolids. In soil column experiments, Al WTR surface applications of 124 and 248 t ha −1 have proven to assist in the reduction of leached P from urban runoff (Ippolito 2015). Similarly, field studies found that Al WTR application at 22.4 dry t ha −1 can reduce leaching of P into shallow groundwaters ).…”
Section: Immobilisation Of Contaminants and Excess Nutrients In Soilmentioning
confidence: 92%
“…millions of tons) of WTRs are produced globally (Babatunde and Zhao, 2007), with the majority disposed of via landfill. However, landfill disposal is increasingly expensive and may be wasting a potentially useable material; an increasing array of potential beneficial uses of WTRs have been researched and demonstrated over the last two decades, including use in constructed reedbeds or as a soil amendment to manage phosphorus (P) mobility within catchments (Babatunde et al, 2011;Ippolito, 2015;Oliver et al, 2011), land application to increase organic matter and water holding capacity and related soil parameters (e.g. Ahmed et al, 1998;Bugbee and Frink, 1985), and most recently as a way of remediating polluted soils through immobilization of contaminants by WTRs (Garau et al, 2014;Garau et al, 2017;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…pH of the WTR samples were determined using 1:1 ratio of WTR to distilled water ( Ippolito, 2015 ). Triplicate beakers containing 10 g of WTR and 10 mL of distilled water were stirred for 15 min.…”
Section: Experimental Methodsmentioning
confidence: 99%